Colivelin, a synthetic derivative of humanin, ameliorates endothelial injury and glycocalyx shedding after sepsis in mice - Urban, Catherine; Hayes, Hannah V.; Piraino, Giovanna; Wolfe, Vivian; Lahni, Patrick; O’Connor, Michael; Phares, Ciara; Zingarelli, Basilia (Frontiers in Immunology, 2022)
Endothelial dysfunction plays a central role in the pathogenesis of sepsis-mediated multiple organ failure. Several clinical and experimental studies have suggested that the glycocalyx is an early target of endothelial injury during an infection. Colivelin, a synthetic derivative of the mitochondrial peptide humanin, has displayed cytoprotective effects in oxidative conditions. In the current study, we aimed to determine the potential therapeutic effects of colivelin in endothelial dysfunction and outcomes of sepsis in vivo. Male C57BL/6 mice were subjected to a clinically relevant model of polymicrobial sepsis by cecal ligation and puncture (CLP) and were treated with vehicle or colivelin (100-200 µg/kg) intraperitoneally at 1 h after CLP. We observed that vehicle-treated mice had early elevation of plasma levels of the adhesion molecules ICAM-1 and P-selectin, the angiogenetic factor endoglin and the glycocalyx syndecan-1 at 6 h after CLP when compared to control mice, while levels of angiopoietin-2, a mediator of microvascular disintegration, and the proprotein convertase subtilisin/kexin type 9, an enzyme implicated in clearance of endotoxins, raised at 18 h after CLP. The early elevation of these endothelial and glycocalyx damage biomarkers coincided with lung histological injury and neutrophil inflammation in lung, liver, and kidneys. At transmission electron microscopy analysis, thoracic aortas of septic mice showed increased glycocalyx breakdown and shedding, and damaged mitochondria in endothelial and smooth muscle cells. Treatment with colivelin ameliorated lung architecture, reduced organ neutrophil infiltration, and attenuated plasma levels of syndecan-1, tumor necrosis factor-α, macrophage inflammatory protein-1α and interleukin-10. These therapeutic effects of colivelin were associated with amelioration of glycocalyx density and mitochondrial structure in the aorta. At molecular analysis, colivelin treatment was associated with inhibition of the signal transducer and activator of transcription 3 and activation of the AMP-activated protein kinase in the aorta and lung. In long-term outcomes studies up to 7 days, co-treatment of colivelin with antimicrobial agents significantly reduced the disease severity score when compared to treatment with antibiotics alone. In conclusion, our data support that damage of the glycocalyx is an early pathogenetic event during sepsis and that colivelin may have therapeutic potential for the treatment of sepsis-associated endothelial dysfunction.